(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Currently sports are growing rapidly and are needed in the field of sports work around the world. This rapid development occurs because more and more research shows the important role of nutrition in maintaining and improving athlete performance. The scope of education for the Association of Indonesian Nutrition Higher Education Institutions (AIPGI) ranges from undergraduate academic education (S1) to stratum 3 (S3), as well as professional education. Until now, it has not been established and there is no specific curriculum for nutrition education in sports. Now there are only sports nutrition courses at undergraduate and postgraduate levels in several tertiary institutions, as well as professional education. In S1 education the scope of competence includes 3 areas, namely; clinical nutrition, community nutrition, and food management. The field of sports nutrition has competence across these areas. Sports nutritionists must have community nutrition competencies to handle healthy athletes who are in training institutions, as well as food management competencies to provide diet or food for athletes. Therefore it is possible that a special competency area will be created for the field of sports nutrition, and will follow the IQF (levels 6-9). Future plans will develop a special education curriculum in the field of sports nutrition in academic education and professional education. The development of professional education in the future is that a Registered Dietitian (RD) can obtain additional degrees or certificates in the specialist practice area (special practitioner), in this case a Registered Dietitian (RD) who focuses on one area of dietetics, such as a Specialist in Sports Dietetics (CSSD). Therefore, it is necessary to develop specialist education for the dietitian profession, including professional education for sports specialist dietitians (SP1; KKNI Level 8) and sub-specialists for certain sports (SP2; KKNI Level 9).